Penerapan Pendekatan Pentahelix Dalam Upaya Pencegahan Terorisme Di Kelurahan Penatoi Kecamatan Mpunda Kota Bima - Burhan; Suparman; Supriadi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Terrorism is now a global threat that involves various aspects of life, transcends national borders, and has become a serious international crime. Indonesia, as a developing country, faces significant threats, especially through bomb terror acts in various regions. The terrorism movement is considered a major threat to humanity that needs to be addressed immediately. This study uses a qualitative method with informants including the village government, community leaders, security forces, and residents of Penatoi Village. Data collection techniques include observation, interviews, and documentation studies. The results of the study show that the strategic role of the village government in preventing terrorism is realized through the pentahelix approach, involving various elements such as Babinsa, Bhabinkamtibmas, religious leaders, and youth leaders. Efforts such as socialization, education on the dangers of terrorism, and provision of basic necessities have succeeded in changing the pattern of community interaction from exclusive to more open, even 80% of residents exposed to radicalism have re-pledged their loyalty to the Republic of Indonesia. Inhibiting factors for the pentahelix approach include budget constraints, dissatisfaction with government assistance, and the existence of underground movements. However, the support of former terrorist convicts as partners and cooperation between the government and various parties, including BNPT and the police, are significant supporting factors in preventing terrorism.